Preparation and characterization of lipopolysaccharide (LPS) monolayers for investigating their role in bacterial adhesion. (2020) - Saini, G.; Wood, B.D.
Abstract: This study was conducted to determine the role played by the length variations and heterogeneous spatial distribution of lipopolysaccharide (LPS) molecules, in gram-negative cells, in mediating adhesion to surfaces. We used extracted LPS molecules from four representative bacterial strains, prepared single molecule thick LPS monolayers using Langmuir-Blodgettry on hydrophobic substrates and used them as model surfaces for AFM studies using nano probes. The prepared LPS monolayers were uniformly distributed over the substrates and enabled preliminary force investigations. Such model monolayers are better alternative to whole-cell analysis and are expected to enable the formulation of an interfacial model for bacterial adhesion.